2010
DOI: 10.1787/hemp-22-5ks5dlhqbfr1
|View full text |Cite
|
Sign up to set email alerts
|

The state of learning outcomes assessment in the United States

Abstract: Worldwide, economic and other factors are pressing institutions of higher education to assess student learning to insure that graduates acquire the skills and competencies demanded in the 21st century. This paper summarises the status of undergraduate student learning outcomes assessment at accredited colleges and universities in the United States. Three-quarters of institutions have established learning outcomes for all their students, a necessary first step in the assessment cycle. Most schools are using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 3 publications
0
51
0
Order By: Relevance
“…In this context, Chun (2010) states that "it is an empty exercise to assess student learning without providing a means to adjust teaching in response to deficiencies revealed through the information gleaned from that assessment". Also, according to Kuh and Ewell (2010), "while there is considerable assessment activity going on, it does not appear that many institutions are using the results effectively to inform curricular modifications or otherwise to enhance teaching and learning". Among other things, Hargreaves (2005) mentions monitoring pupils' performance against targets or objectives and using assessment to inform next steps in teaching and learning as possible meanings for 'assessment for learning'.…”
Section: Attainment Of Student Learning Objectives Through 'Ci'mentioning
confidence: 99%
“…In this context, Chun (2010) states that "it is an empty exercise to assess student learning without providing a means to adjust teaching in response to deficiencies revealed through the information gleaned from that assessment". Also, according to Kuh and Ewell (2010), "while there is considerable assessment activity going on, it does not appear that many institutions are using the results effectively to inform curricular modifications or otherwise to enhance teaching and learning". Among other things, Hargreaves (2005) mentions monitoring pupils' performance against targets or objectives and using assessment to inform next steps in teaching and learning as possible meanings for 'assessment for learning'.…”
Section: Attainment Of Student Learning Objectives Through 'Ci'mentioning
confidence: 99%
“…improvement!and!for!accountability!purposes! (Kuh!&!Ewell,!2010).!!Universities!are!now!being! compared!on!the!results!of!student!performance,!as!well!as!studentHfaculty!ratios!and!number!…”
mentioning
confidence: 99%
“…In Australia, a review of the Australian university quality assurance's audits revealed that most universities failed to incorporate learning outcomes for generic graduate attributes into the curriculum and that the assessment systems in these institutions had failed to affect the learning of these capabilities (Ewan 2009). In the USA, Kuh and Ewell (2010) found that three-quarters of institutions had established learning outcomes for their degree programmes, but the assessment used in these institutions, which was driven by quality assurance, was not used to enhance teaching and learning or to inform curriculum change, evidencing a disconnect between the learning outcomes of university programmes and assessment practices. In engineering and science graduate programmes, Borrego and Cutler (2010) have also found a lack of 'constructive alignment' (Biggs 1999) between learning outcomes, assessment evidence and learning experiences.…”
Section: Literature Reviewmentioning
confidence: 99%